PENGARUH PENGGUNAAN METODE SUGESTOPEDIA TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS X IPA SMA NEGERI 1 KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Wirdalinda, Wirdalinda (Menara Ilmu, 2019)
The Impact of Suggestopedia Methods on the Skill of Writing Short Stories of Students of Class X SMA Negeri 1 Kecamatan Lareh Sago Halaban Sub-District of Lima Puluh Kota".Writing skills one of the active productive language skills.the following method is one of the learning methods that can provide opportunities for success writing writing achievement. This study aims to 1) describe the skills of writing short stories students without using Sugestopedia method of class X students SMA Negeri 1 Kecamatan Lareh Sago Halaban District Lima Puluh Kota; 2) describe the skills of writing short stories using Sugestopedia method of class X students of SMA Negeri 1 Lareh Sago Halaban District, Lima Puluh Kota Regency; 3) to know the influence of Sugestopedia method on the skill of writing short stories of students of grade X SMA Negeri 1 Kecamatan Lareh Sago Halaban District, Lima Puluh Kota District. This research type is quantitative research by using experiment method. In this study used two classes, namely experimental class and control class. Experimental research is an investigation designed in such a way that the phenomenon or event can be disseminated from the influence of other influences. This is evidenced by the change in student scores, which in the control class the mean / mean () is 71.25. After applied Sugestopedia method in learning process in experimental class obtained the change of student learning result with average value () 80,5. Based on t test result(21,31> 1,67) , it is concluded that there is a significant difference between the result of short story writing skill in experiment class using Sugestopedia method and without using suggestion method in control class. This can be seen from the result of comparison of tcount with ttable (21,31> 1,67), because tcount is bigger than ttable then Ha (alternative hypothesis) accepted, it means there is influence of Sugestopedia method in class X SMA Negeri 1 Kecamatan Lareh Sago Halaban District Lima Puluh Kota. Kata kunci: Pengaruh metode Sugestopedia, menulis,cerpen, siswa